PEMBERDAYAAN PENDAMPINGK ABK (ANAK BERKEBUTUHAN KHUSUS) DI UPTD KAMPUNG ANAK NEGERI KALIJUDAN KOTA SURABAYA - Firsty Oktaria Grahani; Ardianti Agustin; Nur Irmayanti; Berliana Nur Chafsah; Diandra Maharani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
The limitations experienced by ABK (Children with Special Needs) are increasingly difficult when they have to face poverty and neglect. To overcome these problems, the Surabaya City Government formed the Service Technical Implementation Unit (UPTD) of Kampung Anak Negeri Kalijudan to accommodate ABK and provide guidance, with the aim of restoring a sense of self-esteem, self-confidence and social responsibility, and being able to carry out normal social functions in life. Public. Coaching is carried out by assistants. The role of the assistant in the UPTD of the Kalijudan Children's Village is very large, for the effectiveness of the coaching program carried out. The problem is that the various scientific backgrounds of the assistants are even less relevant to the profession they are in, the lack of understanding of the optimization of effective coaching tailored to the special needs of residents and the limited knowledge of ABK so that the mentoring process is only limited to self-development training. The goal is that mentors better understand the variety of special needs both in terms of types, characteristics and interventions, are more aware and sensitive to every behavior that appears and effective handling patterns to be carried out, and assistants actively contribute to innovating in designing activities in the ABK development process and implementing become a regular activity. The implementation method used is education about ABK and skill development in handling ABK according to its characteristics, making development achievement targets for each ABK. Keywords: Empowerment of companions, Children with Special Needs (ABK)